Analysis of Chemistry Problem-Solving Ability in Symbolic Level for Senior High School Students - Rudi, La; Haetami, Aceng; Asria, Asria; Shuid, Ahmad Naqib bin (Jurnal Pendidikan Progresif, 2023)
Objective: The study aims to analyzing the Ability to Solve Symbolic Level Chemistry Problems on Buffer Solution Material at SMA Negeri 1 Mawasangka Tengah aims to determine the ability to solve symbolic level chemistry problems and responses of MIPA XI class students to Three Tier Multiple Choice questions on buffer solution material. Method: This research method using descriptive qualitative method. The entire population in this study was used as a sample, namely all students of class XI MIPA, totaling 60 students. Data collection was carried out using a Three Tier Multiple Choice diagnostic test and a student response questionnaire. Finding: The results showed that the ability to solve symbolic level chemistry problems on buffer solution material was still low, with an average percentage of understanding the concept of 9.77%, misconceptions of 57.75%, and not understanding the concept of 32.48%. Students' responses to the use of three-tier multiple-choice questions were positive, with a percentage of 74.30%; students gave good responses to the three-tier test, so this form of test is categorized as good to identify the level of student understanding in solving symbolic level chemistry problems on buffer solution material. Concusion: From the results of the analysis, it can be concluded that the diagnostic three-tier test is one of the good test forms to find out about problem-solving skills in the form of problems. Keywords: chemistry problem solving ability, symbolic, three tier multiple choiceDOI: http://dx.doi.org/10.23960/jpp.v13.i1.202310